Enhanced Catalytic Performances for Guaiacol Aqueous Phase Hydrogenation over Ruthenium Supported on Mesoporous TiO2 Hollow Spheres Embedded with SiO2 Nanoparticles. Issue 29 (18th October 2017) - Han, Bingbing; Bao, Zhikang; Liu, Tianzhu; Zhou, Hu; Zhuang, Guilin; Zhong, Xing; Deng, Shengwei; Wang, Jianguo
Abstract: The catalytic hydrogenation of lignin‐derived phenolic compounds with high catalytic activity and yield is important for the efficient utilization of lignin derivatives. In this study, a series of mesoporous TiO2 sphere‐supported Ru catalysts were prepared, characterized, and used for hydrogenating guaiacol in aqueous solutions. Both the 100% conversion and 84.2% cyclohexanol yield were achieved using Ru supported on mesoporous TiO2 hollow spheres embedded with SiO2 nanoparticles (Ru‐TiO2 ‐eSiO2 ) catalyst under 1.5 MPa H2 at 160 °C for 100 min. Catalyst characterization indicated that the outstanding catalytic performance of the Ru‐TiO2 ‐eSiO2 is mainly due to its unique spherical structure and acidic properties. The TiO2 shell is polyporous with numerous 3.8 nm mesopores that favor mass transfer efficiency in the reaction process. Moreover, the moderate acidic sites of the catalyst promoted the removal of the –OCH3 group from guaiacol and improve cyclohexanol yield. The catalyst exhibited good water resistance and its catalytic activity presented no obvious loss after recycling for 5 times. Abstract : Both the 100% conversion and 84.2% cyclohexanol yield were achieved using Ru supported on mesoporous TiO2 hollow spheres embedded with SiO2 nanoparticles catalyst for guaiacol aqueous phase hydrogenation under 1.5 MPa H2 at 160 °C. Detailed characterization suggested that the unique spherical structure is main reason for the high catalytic activity, which favors the mass transfer and provides more active sites on the outer and inner surfaces of the catalyst.